Cannabinoid CB1 Receptor Agonists Do Not Decrease, but may Increase Acoustic Trauma-Induced Tinnitus in Rats - Zheng, Yiwen; Reid, Peter; Smith, Paul F. (Frontiers in Neurology, 2015)
Tinnitus has been suggested to arise from neuronal hyperactivity in auditory areas of the brain and anti-epileptic drugs are sometimes used to provide relief from tinnitus. Recently, the anti-epileptic properties of the cannabinoid drugs have gained increasing interest; however, the use of cannabinoids as a form of treatment for tinnitus is controversial. In the present study, we tested whether a combination of delta-9-tetrahydrocannabinol (delta-9-THC) and cannabidiol (CBD), delivered in a 1:1 ratio, could affect tinnitus perception in a rat model of acoustic trauma-induced tinnitus. Following sham treatment or acoustic trauma, the animals were divided into the following groups: 1) sham (i.e. no acoustic trauma) with vehicle treatment; 2) sham with drug treatment (i.e. delta-9-THC + CBD); 3) acoustic trauma-exposed exhibiting tinnitus, with drug treatment; and 4) acoustic trauma-exposed exhibiting no tinnitus, with drug treatment. The animals received either the vehicle or the cannabinoid drugs every day, 30 min before the tinnitus behavioural testing. Acoustic trauma caused a significant increase in the auditory brainstem response (ABR) thresholds in the exposed animals, indicating hearing loss; however, there was a partial recovery over 6 months. Acoustic trauma did not always result in tinnitus; however among those that did exhibit tinnitus, some of them had tinnitus at multiple frequencies while others had it only at a single frequency. The cannabinoids significantly increased the number of tinnitus animals in the exposed-tinnitus group, but not in the sham group. The results suggest that cannabinoids may promote the development of tinnitus, especially when there is pre-existing hearing damage.